A Clinical Study Of Shvitra (Lucoderma) And Its Management Through Shamshamanachikitsa – A Case Study - Chowdhury, Nur Mohammad Iqbal; Pinkee; Sahu, Ajay Kumar; Joshi, Ram Kishor (International Research Journal of Ayurveda & Yoga, 2024)
Lucoderma/ vitiligoare acquired depigmentation of skin. It affects 1% of the world’s population. Various hypotheses to suggest the aetiology of vitiligo have been put forward with different mechanism coming into play in different cases.Autoimmune hypothesis is based on the clinical association of vitiligo with a number of disorders considered to be autoimmune (e.g., thyroid disease, Additions disease, diabetes mellitus etc.). Organ- specific antibodies to thyroid, gastric parietal cells and adrenal tissue are found in the serum more frequently in the patients with vitiligo than general population.The disease presents are well- defined hypo- or depigmented macule or patch without any change in the texture of skin1,2According to vernacular, it is called Shvetakushtha it is described under the chapter of Kushtharoga in chief Ayurveda texts. Shwetakushtha is also called as Shvitra and it is caused by various dietetic and behavioural factors which aggravate the tridosha, especially the kapahadosha vitiating the rakta, mamsaandmedadhatu3,4,5,. Here the case presentation of a female (unmarried) has age 20 years old. The treatment was for 3 month regular follow up.